Thursday
March 23, 2017

Post a New Question

Posted by on Tuesday, September 13, 2011 at 10:52am.

Perform the indicated operation(s) and express the result in standard form. Leave answers in terms of square roots (do not use decimals).
(-9-sqrt-3)^2

  • math - , Wednesday, September 14, 2011 at 9:10pm

    (-9 - sqrt(-3))^2 =
    (-9 - sqrt(3*-1)^2=
    (-9 - isqrt(3))^2 =
    81 + 18isqrt3 + 3 =
    3(27 + 6isqrt3 + 1).

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question